Direct Display Interaction via Simultaneous Pen + Multi-touch Input - Hinckley, Ken; Pahud, Michel; Buxton, Bill (Society for Information Display (SID) Symposium Digest of Technical Papers, 2010)
Current developments hint at a rapidly approaching future where simultaneous pen + multi-touch input becomes the gold standard for direct interaction on displays. We are motivated by a desire to extend pen and multi-touch input modalities, including their use in concert, to enable users to take better advantage of each.